The Application of Bactericidal Silver Nanoparticles in Wound Treatment - Geewoo Nam; Sabarinathan Rangasamy; Baskaran Purushothaman; Joon Myong Song (Nanomaterials and Nanotechnology, 2015)
Even with the prevalence of wounds, the medical technol‐ ogy for efficiently managing skin damage is still primitive. The disruption of any of the numerous healing processes can lead to problems in the time-sensitive healing actions of the dermal and epidermal layers. Bacterial infection is one of the major obstacles to proper wound healing as it poses a danger of causing long-term negative effects. Keeping the wound free of bacteria is imperative to the proper and hasty repair of dermal wounds. Silver has been widely used to treat wounds for its bactericidal properties. Although the mechanism of silver’s antibacterial action is not fully understood, it exhibits a significant antimicrobial efficacy against a wide spectrum of bacterial species. A number of different approaches to the mechanism are reported and presented in this review. Silver nanoparticles (AgNPs) have been reported to exhibit enhanced antibac‐ terial activity due to their increased surface-area-to-volume ratio. AgNPs are capable of various modifications, signifi‐ cantly broadening the therapeutic properties of the mate‐ rial as a result. This review explores the different aspects of silver and silver nanoparticles, and their antibacterial properties, which can be applied in the field of wound treatments.